Diseño de un modelo de gestión por procesos para mejorar la atención al público en el departamento de tesorería del GAD M-Montecristi, 2014 - Quijije Mero, Verónica Elizabeth (2014)
This research presents a proposal of a model of management processes for the Department of Treasury of the GAD M-Montecristi whose objective is to improve the service offered to the public; any time that the service the customer is part of the image that projected the institution and is perceived as strength for creating and maintaining long-lasting relationships. Analyzed the current situation coming to the conclusion that does not satisfy the needs of internal and external customer, being necessary to improve it in order to strengthen assistance to the user an efficient and quality, since for the public sector, the objective of market is the community. The proposed work will serve as input necessary contribution to the Department of Treasury of the GAD M-Montecristi, people who are engaged day by day in providing service to the public, under the condition that it must provide a service with efficiency, effectiveness, economy and ethics, taking into consideration legal regimes that are in force in the country.